Factores psicosociales inmersos en el proceso de resocialización de las personas condenadas del establecimiento penitenciario de mediana seguridad y carcelario EPSMSC, de Buenaventura, año 2023 (2023)
The main objective of this project was to describe the psychosocial factors that are immersed in the process of resocialization of convicted persons from the EPMSC Medium Security Penitentiary and Prison, in Buenaventura, in 2023. The methodology used experimental design and analytical empirical epistemological criteria.